Analisis upaya pemenuhan kebutuhan bertingkat tokoh jadag dalam film Turah 2016 - Prasetio, Anggih; Harini, Yostiani Noor Asmi (Universitas Lampung, 2023)
This study aims to identify the humanistic aspects that experienced by the character Jadag in the film “Turah”. This research using descriptive qualitative method with data collection techniques observative and using Maslow's theory in identifying the humanistic aspects experienced. The data in this study is a conversation and the behavior of the character Jadag in the film “Turah”. This research focuses on the efforts of Jadag leaders in meeting multilevel needs. Research result shows that the character Jadag in the film